Ludic adaptation: can we babyfy, chibify, bambify, or cherubify a literary text for younger audiences? - Purnomo, SF. Luthfie Arguby; Untari, Lilik Untari; Purnama, SF. Lukfianka Sanjaya; Nur Asiyah,; Umam, Robith Khoiril; Sartika, Yustin; Novianni Anggraini,; Elen Inderasari, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Studies on adaptation for younger audiences tend to mull over around the film adaptation of children classics. Adaptation of textual, visual, and operative elements for younger audiences in the context of literary texts with ergodicity like apps, comics, animation films, and games is understudied. This case study based descriptive qualitative study aims at exploring and investigating the phenomenon and how this adaptation is exercised. This study employs Siddharthan’s text simplification, Genette’s hypertextuality, Nikolajeva’s Barthesian proairetic decoding for younger audiences, and Huizinga’s play-function and play-mood to address the language aspects of ludic adaptation, Aarseth’s ergodic literature and Sander’s adaptation to address the literary aspects, and Rajewsky’s intermediality to address the medial aspects. Drawing upon the theories and employing Spradleyan analysis, we argue that adaptation for younger audiences is best termed ludic adaptation, an adaptation aimed at establishing a playful communication involving textual, visual, and operative adjustments for younger audiences through transmodalization, transstylization, and transformation of the source texts. In adapting the apps, comics, animation films, and games into their simplified versions, the adapters employ what we call as babyfication, chibification, bambification, and cherubification. Scholars of language and literary studies might apply ludic adaptation to reveal how adaptation for younger audiences is carried out. App, comic, animation film, and game adaptation practitioners might employ ludic adaptation as a guideline in their process of adapting these literary texts.